ANALISIS DAMPAK PENERAPAN PSAK 73 TERHADAP KINERJA KEUANGAN PERUSAHAAN RITEL YANG TERDAFTAR DI BEI - Deviana, Cut; Sebayang, Minda Muliana Br; Siregar, Retnawati (Gapenas Publisher, 2025)
Indonesian Accounting Standard Board published PSAK 73 to replace the existing lease PSAK 30, effective from 1 January 2020. There is only be one single model to recognize lease, a in lessee’s book which requires lessee to record all lease transactions as right-use assets and leases liabilities. The purpose of this study is to analyze the impact of the implementation of PSAK 73 on the financial position statements and financial ratios retail companies listed on the Indonesia Stock Exchange in 2018 and 2019. This study uses a quantitative descriptive approach by applying the constructive lease capitalization method. The samples in this research are retail companies listed on the BEI in 2018 dan 2019 according to predetermined criteria, namely PT Matahari Departement Store dan PT Matahari Putra Prima Tbk. The results of the study indicate that the implementation of PSAK 73 has an effect on the financial position statements and income statements of retail companies. In the financial position statement, the value of assets and liabilities has increased significantly, while equity has decreased significantly. In the income statement, there has been an increase in total profit. ROA ratios, ROE ratios, DAR ratios, and DER ratios, increased after the application of PSAK 73 on leases.